Role of the Ionospheric Conductance Profile in Sub‐Alfvénic Moon‐Magnetosphere Interactions: An Analytical Model. Issue 7 (6th July 2021) - Simon, Sven; Liuzzo, Lucas; Addison, Peter
Abstract: We develop an analytical model of the Alfvén wings generated by the interaction between a moon's ionosphere and its sub‐Alfvénic magnetospheric environment. Our approach takes into account a realistic representation of the ionospheric Pedersen conductance profile that typically reaches a local minimum above the moon's poles and maximizes along the bundle of magnetospheric field lines tangential to the surface. By solving the equation for the electrostatic potential, we obtain expressions for various quantities characterizing the interaction, such as the number flux and energy deposition of magnetospheric plasma onto the surface, the spatial distribution of currents within the Alfvén wings and associated magnetic field perturbations, as well as the Poynting flux transmitted along the wings. Our major findings are: (a) Deflection of the magnetospheric plasma around the Alfvén wings can reduce the number flux onto the surface by several orders of magnitude. However, the Alfvénic interaction alone does not alter the qualitative shape of the "bullseye"‐like precipitation pattern formed without the plasma interaction. (b) Due to the deflection of the upstream plasma, the energy deposition onto the moon's exosphere achieves its minimum near the ramside apex and maximizes along the flanks of the interaction region. (c) Even when the ionospheric conductance profile is continuous, the currents along the Alfvén wings exhibit several sharp jumps. These discontinuities generate spikes in the magnetic field that are still observable at large distances to the moon. (d) The magnitude and direction of the wing‐aligned currents are determined by the slope of the ionospheric conductance profile. Key Points: We calculate the flow deflection, electric currents, and plasma and energy flux patterns for sub‐Alfvénic moon‐magnetosphere interactions The number flux of the magnetospheric flow peaks above the obstacle's ramside apex, but the energy flux achieves its minimum in that region The currents along the Alfven wing characteristics exhibit several sharp jumps, generating observable spikes in the magnetic field